علاقة سدّ الذرائع بالمفاهيم الأساسية في التشريع الإسلامي - Abdul Hai Al-Madni; Muhammad Idrees Lodhi (Pakistan Journal of Islamic Research)
This article aims to show that Islam as a religion is just not a set of some rituals but a complete way of life.  In the final moments of the holy prophet (peace be upon him) the Qur’ān declares the same claim in its words like “This day I have perfected for you your religion and completed My favor upon you and have approved for you Islam as religion (Al-Māʼidah:3).  So, in other words, this announcement means that in the light of the Qur’ān and Sunnah, Islam has the solution of all the prevailing problems and occurrences till the last day. Having great insight and depth in the Qur’ān and Sunnah the theologians and scholars have devised some rules and guidelines regarding such modern issues and occurrences.  In religious terminology, it is called, Usūl-al-Fiqh which has some fundamental and supplementary sources. Among these supplementary sources is Sad-al-Dharāʼayʽ. For seeking new solutions, all the scholars have relied upon these supplementary sources. Sad means to close down something and Dharāʼayʽ means to extract something. In Islamic jurisprudence, Dharāʼayʽ means a cause or a motive leading to any unlawful Haram act. So, Sad-al-Dharāʼayʽ means to stop and prohibit form those sources which lead to some Haram or prohibited act. Keeping in view the pervious details the first chapter of this article focuses on the linguistic and religious meaning of Dharāʼayʽ and the five types of Dharāʼayʽ.The second chapter has the discussions regarding the relationship between the fundamental meanings of Islamic Sharia and the principle of Sad-al-Dharāʼayʽ The last chapter of the article is included some examples of practical implications of the given principle Sad-al-Dharāʼayʽ for solving the contemporary issues.